LEAVING A MARK IN ARGENTINA. THE DIPLOMATIC STAY OF ALFONSO REYES THROUGH CULTURAL AND LITERARY MAGAZINES (Tzintzun, Revista de Estudios Históricos, 2022)
This article examines the presence of the Mexican writer Alfonso Reyes in Argentine cultural magazines during his diplomatic stay in this country (1927- 1930 and 1936-1938). The analysis of the discursive and iconographic representations allows for the unraveling of the meanings associated with his diplomatic mission and the consideration of the transfers between public opinion and circles of intellectual sociability. It is argued that on most occasions the interpretations accentuated his double representation as a diplomatic writer. To this end, we sought to elucidate the connotations in the Argentine cultural and political field.
Keywords: Alfonso Reyes in Argentina; cultural diplomacy; ultural and literary magazines; Mexico-Argentina